THE HISTORICAL DEVELOPMENT AND CURRENT TRENDS OF POLITICAL SCIENCE AS A FIELD OF STUDY IN NIGERIA - Toye Manuwa (International Studies Journal)
This study provides an overview of the historical development and current trends of political science as a field of study in Nigeria. It examines how political science emerged and evolved as a distinct academic discipline in Nigeria after its independence from British colonial rule. It explores the main subfields, approaches, theories, and methods of political science in Nigeria, such as comparative politics, political economy, political sociology, political behavior, public administration, international relations, and political philosophy. It investigates the current challenges and opportunities for political science in Nigeria in the 21st century, such as democratization, development, security, corruption, ethnicity, and globalization. It assesses how political science relates to other disciplines and to public policy by providing analytical tools and empirical evidence for understanding and addressing political issues and problems. In conclusion, this study highlights the importance and relevance of political science as a field of study in Nigeria and beyond.